Permeability Profiles Across the Crust‐Mantle Sections in the Oman Drilling Project Inferred From Dry and Wet Resistivity Data. Issue 8 (31st July 2020) - Katayama, Ikuo; Abe, Natsue; Hatakeyama, Kohei; Akamatsu, Yuya; Okazaki, Keishi; Ulven, Ole Ivar; Hong, Gilbert; Zhu, Wenlu; Cordonnier, Benoit; Michibayashi, Katsuyoshi; Godard, Marguerite; Kelemen, Peter; et al.
Abstract: Permeability profiles in the crust‐mantle sequences of the Samail ophiolite were constructed based on onboard measurements of the electrical resistivity of cores recovered during the Oman Drilling Project. For each sample, we measured dry and brine‐saturated resistivity during the description campaign on the drilling vessel Chikyu . Owing to the conductive brine in the pore space, wet resistivity is systematically lower than dry resistivity. The difference between dry and wet resistivity is attributed to the movement of dissolved ions in brine that occupies the pore space. We applied effective medium theory to calculate the volume fraction of pores that contribute to electrical transport. Using an empirical cubic law between transport porosity and permeability, we constructed permeability profiles for the crust‐mantle transition zone and the serpentinized mantle sections in the Samail ophiolite. The results indicate that (1) the gabbro sequence has a markedly lower permeability than the underlying mantle sequence; (2) serpentinized dunites have higher permeability than serpentinized harzburgites; and (3) discrete sample permeability is correlated with ultrasonic velocity, suggesting that the permeability variations predominately reflect crack density and geometry. Plain Language Summary: Aqueous fluids that circulated beneath the seafloor play an important role in heat transfer, chemical exchange, and microbial activity in the oceanic lithosphere. The Oman Drilling Project was successful in obtaining continuous drill cores through the crust‐mantle sequences in the Samail ophiolite, where the paleo‐oceanic basement was thrust onto the continental crust in the Late Cretaceous. In this study, we constructed profiles of permeability across the crust‐mantle sections using the effective medium theory and resistivity data, which provide insights into fluid circulation in the oceanic lithosphere. The results indicate higher permeability in the uppermost mantle sequence between the crust and the underlying mantle, suggesting that present‐day fluid transfer is predominant at the crust‐mantle boundary. Although the fluid flow and chemical reactions are likely coupled, the high permeability could promote the transformation of crust‐mantle materials and hence the recycling of water into the mantle. Application of this technique to forthcoming deep drilling projects through the Mohorovičić discontinuity (Moho) and into the upper mantle may provide insights into the permeability structure and fluid circulation system in the oceanic lithosphere. Key Points: Brine‐saturated resistivity is systematically lower than dry resistivity, with the differences attributed to the volume fraction of pores Permeability through the crust‐mantle sequences was modeled using the effective medium theory and resistivity data The dunite sequence is characterized by higher permeability than the overlying gabbro and underlying harzburgite sequences